Uses and Gratifications, Journalists' Twitter Use, and Relational Satisfaction with the Public. Issue 3 (2nd July 2016) - Kim, Yonghwan; Kim, Youngju; Wang, Yuan; Lee, Na Yeon
Abstract : This study employed the uses and gratification approach to investigate how journalists perceive relational satisfaction with the public on Twitter, specifically the associations between journalists' motivations to use Twitter, their Twitter use, and their relational satisfaction with the public. Through a survey of South Korean journalists, this study revealed that journalists' motivations for Twitter use are positively related to their job-related activities on Twitter (e.g., posting/sharing their news and interacting with audience), which consequently influences perceived relational satisfaction with the public. The findings provide new insight into an increasingly important part of the public's engagement and news/information flows in the digital media environment. This study expands upon the literature by analyzing how journalists' motivations for using Twitter and their job-related activities on Twitter are associated with relational satisfaction with the public.